Computational modeling of a Novel CTX-M β-lactamase Escherichia coliisolated from Yogyakarta, Indonesia Using I-TASSER and SWISS-MODEL - Anggiresti Kinasih; Endah Retnaningrum (Universitas Nahdlatul Ulama Surabaya, 2026)
Extended-spectrum β-lactamases (ESBLs), especially those of the CTX-M family, significantly contribute to antibiotic resistance in Escherichia coli. While CTX-M variants are well-characterized in clinical settings, their structural features in foodborne E. coli remain underexplored, particularly in countries like Indonesia. This study aimed to predict and validate the three-dimensional (3D) structure of a novel CTX-M β-lactamase protein from an E. coli isolate (D4DU2-ESBL-EC) culture collection at Laboratory of Microbiology, Universitas Gadjah Mada (UGM). This study reports a novel CTX-M variant from E. coli D4DU2, a locally strain originated from raw chicken meat in Yogyakarta traditional market that has been shown to adapt and thrive in Sleman Regency, Indonesia. Based on phylogenetic and structural analyses, E. coli D4DU2 evolutionary link to Indian CTX-M-15, with distinct mutations at W253L, P254A amino acid near the active site. The 3D structure of D4DU2 CTX-M β-lactamase was predicted using I-TASSER and validated using PROCHECK. Ramachandran analysis showed 78.4% of residues in the most favored regions, 20.5% in allowed regions, and only 1.2% in disallowed regions, confirming high stereochemical quality. These findings highlight potential local adaptation and emergence of a unique ESBL-producing E. coli strain. This study provides a reliable model for CTX-M β-lactamase from foodborne E. coli in Indonesia, supporting One Health-based surveillance and intervention strategies. Overall, this study demonstrates that I-TASSER, complemented by PROCHECK validation, offers a valuable in silico approach for the structural characterization of ESBL proteins from foodborne bacterial isolates in resource-limited contexts